Winners and Losers in Post COVID-19 Business World, the New Norm for Malaysia - Karthigayan Gunasegaran; Che Zalina Zulkifli; Sivaganesh Loganathan; Mohd Fauzi Sedon (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The purpose of this study is to explore and analyze winners and losers in the post-covid-19 business world, the new norm for Malaysia. Design/methodology/approach: This study uses a literature research model, which is to collect various kinds of data and literature then take the essence of the data and literature then describe and analyze it. Findings: COVID-19 pandemic manifested at the time when mankind was least prepared to face it. This virus has permanently altered the fabric of the globalized world. The global damages inflicted by this pandemic go beyond loss of lives in multitudes, but also quality of living. While government around the world are battling to contain the virus for the safety of its people, there is a pressing need to start thinking about a world that will be living with the after effects of COVID-19.The global economy is going to shrink drastically and Malaysia will not be spared. The damage will be irreversible should all measures to contain the virus fail. Taking into account various scenario modeling from credible sources, a list of winners and losers in post COVID-19 business world has been derived. The reality of this pandemic demands the business world to embark on an accelerated shift towards being innovative, digital, pro-active and pre-emptive. Research limitations/implications: This research uses secondary data. Practical implications: Business entities can use the result of research as consideration so that the business can still exist. Originality/value: This research explores the phenomena of covid 19 in Malaysia and the impact on business. Paper type: Research paper.